A cancer‐associated CDKN1B mutation induces p27 phosphorylation on a novel residue: a new mechanism for tumor suppressor loss‐of‐function. Issue 4 (6th February 2021) - Bencivenga, Debora; Stampone, Emanuela; Aulitto, Arianna; Tramontano, Annunziata; Barone, Clementina; Negri, Aide; Roberti, Domenico; Perrotta, Silverio; Della Ragione, Fulvio; Borriello, Adriana
Abstract : CDKN1B haploinsufficiency promotes the development of several human cancers. The gene encodes p27 Kip1, a protein playing pivotal roles in the control of growth, differentiation, cytoskeleton dynamics, and cytokinesis. CDKN1B haploinsufficiency has been associated with chromosomal or gene aberrations. However, very few data exist on the mechanisms by which CDKN1B missense mutations facilitate carcinogenesis. Here, we report a functional study on a cancer‐associated germinal p27 Kip1 variant, namely glycine9‐>arginine‐p27 Kip1 (G9R‐p27 Kip1 ) identified in a parathyroid adenoma. We unexpectedly found that G9R‐p27 Kip1 lacks the major tumor suppressor activities of p27 Kip1 including its antiproliferative and pro‐apoptotic functions. In addition, G9R‐p27 Kip1 transfection in cell lines induces the formation of more numerous and larger spheres when compared to wild‐type p27 Kip1 ‐transfected cells. We demonstrated that the mutation creates a consensus sequence for basophilic kinases causing a massive phosphorylation of G9R‐p27 Kip1 on S12, a residue normally never found modified in p27 Kip1 . The novel S12 phosphorylation appears responsible for the loss of function of G9R‐p27 Kip1 since S12AG9R‐p27 Kip1 recovers most of the p27 Kip1 tumor suppressor activities. In addition, the expression of the phosphomimetic S12D‐p27 Kip1 recapitulates G9R‐p27 Kip1 properties. Mechanistically, S12 phosphorylation enhances the nuclear localization of the mutant protein and also reduces its cyclin‐dependent kinase (CDK)2/CDK1 inhibition activity. To our knowledge, this is the first reported case of quantitative phosphorylation of a p27 Kip1 variant on a physiologically unmodified residue associated with the loss of several tumor suppressor activities. In addition, our findings demonstrate that haploinsufficiency might be due to unpredictable post‐translational modifications due to generation of novel consensus sequences by cancer‐associated missense mutations. Abstract : CDKN1B, encoding p27 Kip1, is mutated in human cancers. We demonstrate that c.25G>A (p.G9R) CDKN1B mutation, identified in a parathyroid adenoma, generates a new consensus sequence for R‐directed kinases causing p27 Kip1 phosphorylation on a residue (S12) physiologically unphosphorylated. The unexpected phosphorylation, reducing p27 Kip1 ‐dependent cyclin‐dependent kinase inhibition, enhances protein degradation and reduces p27 Kip1 anticancer activities. Our study unveils an unreported mechanism of tumor suppressor haploinsufficiency.